China's foray into Africa: ideational underpinnings and geoeconomic interests - Mensah, Chaldeans (My University, 2010)
China’s new foreign policy stance in Africa is a marked departure from its previous emphasis on purely ideational principles designed to strengthen its standing as a supporter of the Third World. The ideational affinity with Africa has not changed in China’s foreign policy discourse, but the new emphasis is on an aggressive pursuit of its geoeconomic and geopolitical interests on the continent, marked by an acquisitive impulse for Africa’s natural resources and a concerted effort to offer political support to its allies in Africa to secure those resources in an uncertain post bipolar international system. This paper explores the transformation of China’s African policy, ideationally, from the Bandung principles to the Beijing Consensus, while noting the geoeconomic and geopolitical motivations behind China’s engagement with Africa as it cements its position as an emerging global power. The paper concludes that despite the presumed coincidence of interests and ideational affinity that formed the basis of pre-Deng China-Africa relations, China’s new geoeconomic and geopolitical engagement represents a major pathway for the continent, but serious steps must be taken to harness the relationship to ensure that it fulfils Africa’s desire to pursue a sustainable development agenda that moves it away from overdependence on commodity exports and marginality in the global economy. A version of this paper was presented in July 2008 at the Second Global Studies Conference in Ljubljana, Slovenia.
Keywords: Beijing consensus; geoeconomics; geopolitics; hard power; natural resources; soft power; South-South cooperation